Effects of an ankle brace on the in vivo kinematics of patients with chronic ankle instability during walking on an inversion platform - Cao, Shengxuan; Wang, Chen; Zhang, Gonghao; Ma, Xin; Wang, Xu; Huang, Jiazhang; Zhang, Chao; Wang, Kan (Gait & posture, 2019)
•Tibiotalar and subtalar kinematics were studied.•Individuals with ankle instability exhibited increased subtalar inversion.•Ankle brace reduced subtalar inversion when walking on an inverted surface. As in vivo tibiotalar and subtalar joint kinematics are not currently known following the application of an ankle brace, an investigation of these kinematics may provide insight into the mechanisms of ankle braces. This study aimed to determine the effect of an ankle brace on in vivo kinematics of patients with chronic ankle instability. Eleven patients with chronic ankle instability were recruited in this study. A dual fluoroscopic imaging system and a solid modeling software were utilized to calculate the joint positions of the participants as they walked barefooted on a level platform, walked barefooted on a 15° inversion platform, and walked with an ankle brace on a 15° inversion platform. The joint positions during the three walking conditions were compared. Tibiotalar joints were more inverted (pose 2, p = .004), and subtalar joints were more anteriorly translated (pose 2–6, p = .003), more plantarflexed (pose 2, p = .008; pose 3, p = .013; pose 5, p = .008; pose 6, p = .016) and more inverted (pose 1–5, p = .003; pose 6, p = .013) during barefooted walking on the inversion platform than during walking on the level platform. The inversion of subtalar joints was decreased after the brace application (pose 2–4, p = .003; pose 5, p = .004; pose 7, p = .016). Brace application reduced the increased subtalar inversion induced by the inversion platform. Nevertheless, increased subtalar anterior translation and plantarflexion persisted after brace application. The ankle brace might be beneficial for clinical populations with increased subtalar inversion.